Analysis of the Implementation of Village Funds Sourced from the State Budget in Banjarnegara Regency - Enceng; Zulham Adamy; Maman Sudirman (CV. Multi Kreasi Media, 2023)
This study aims to analyze how the implementation of Government Regulation Number 22 of 2015 concerning Amendments to Government Regulation Number 60 of 2014 for village funds originates from the State Revenue and Expenditure Budget (APBN). This study uses Grindle's theory, namely that policies depend on their content and context, and their level of success depends on the conditions of the three component variables of implementation resources: factors of power, interests, and the strategies of the actors involved; characteristics of institutions and authorities; and decision and responsiveness. The research method used is a descriptive comparative with five villages (Kalilunjar Village, Gentansari Village, Giritirta Village, Kebutuhduwur Village, and Pesangkalan Village) as research subjects. The study results show that from the aspect of power, the characteristics of institutions and authorities, decisions and responsiveness, and resources have gone well. The five villages also have the potential to become tourist villages. The implementation of village funds is intended for the realization of advanced, robust, independent, and prosperous villages and village communities.